The epistolary novel : representations of consciousness - Bray, Joe (Routledge studies in eighteenth-century literature, 2003)
This book argues that the way the eighteenth-century epistolary novel represented consciousness had a significant influence on the later novel, a view that had been largely ignored in most accounts of the development of the novel.